Kemampuan Membaca Bahasa Mandarin Siswa Sekolah Dasar - S, Jumarni; Saud, Syukur; Sukmawaty, Sukmawaty (Universitas Negeri Makassar, 2021)
Abstract. This study aims to describe the students' ability to read Mandarin (hanzi and pinyin) in terms of intonation, pronunciation, and fluency. The subjects of this study were 16 students of grade V SD Frater Makassar in 2020. The data analysis technique was quantitative descriptive. Quantitative analysis was obtained through observation and documentation activities. Based on the results of this study, the reading ability of the fifth grade students of SD Frater Makassar from the assessment of intonation, fluency, and pronunciation aspects, was still in the less category, which could be seen from the overall score of 1000 students with an average score. -Average 62.5 and a percentage value of 69.4%, Indonesian / Indonesian language grammar affects students in speaking Mandarin.